2017
DOI: 10.1080/09553002.2017.1321806
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose rate affects the radiosensitization of MCF-7 and HeLa cell lines to X-rays induced by dextran-coated iron oxide nanoparticles

Abstract: Increasing the dose rate of 6 MV photons irradiation in MCF-7 and HeLa cells increases the radiosensitization induced by the dextran-coated iron nanoparticles in these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
0
9
2
Order By: Relevance
“…The most significant effects were seen in MCF7 and HEPG2 cells (P < 0.0001). These data are in contrast to a previous study by Khoshgard et al which reported no cytotoxicity for SPIONs following 24 h exposures in MCF7 and HeLa cells, using an MTT assay [67]. Also, the inherent cytotoxicity observed in our study did not correlate DNA damage, suggesting that it is possible that in cell lines other than U87 and HEPG2, any decrease in cell survival post-irradiation was due to radiosensitisation, along with other possible causes of DNA damage.…”
Section: Discussioncontrasting
confidence: 99%
“…The most significant effects were seen in MCF7 and HEPG2 cells (P < 0.0001). These data are in contrast to a previous study by Khoshgard et al which reported no cytotoxicity for SPIONs following 24 h exposures in MCF7 and HeLa cells, using an MTT assay [67]. Also, the inherent cytotoxicity observed in our study did not correlate DNA damage, suggesting that it is possible that in cell lines other than U87 and HEPG2, any decrease in cell survival post-irradiation was due to radiosensitisation, along with other possible causes of DNA damage.…”
Section: Discussioncontrasting
confidence: 99%
“…The most significant effects were seen in MCF7 and HEPG2 cells (P < 0.0001). These data are in contrast to a previous study by Khoshgard et al which reported no cytotoxicity for SPIONs following 24 hr exposures in MCF7 and HeLa cells, using an MTT assay(60). Also, the inherent cytotoxicity observed in our study did not correlate DNA damage, suggesting that in cell lines other than U87 and HEPG2, any decrease in cell survival post-irradiation was due to radiosensitisationThe impact of combinations of SPIONs with radiation on DNA damage yields is presented inFigure 3.…”
contrasting
confidence: 99%
“…Cell survival curves from Figure7to 10 showed that MCF-7 cells experienced more death compared to HeLa cells when irradiated with photon and electron beam. These results indicated that the Bi 2 O 3 -NR influenced radiosensitization more in MCF-7 cells Khoshgard (2017). reported that dextran-coated iron oxide nanoparticles increase the effect of radiosensitivity when irradiated with a 6 MV photon beam.…”
mentioning
confidence: 77%
“…reported that dextran-coated iron oxide nanoparticles increase the effect of radiosensitivity when irradiated with a 6 MV photon beam. It was discovered from the study that MCF-7 cells produced higher SER values (1.21 ± 0.06) compared to HeLa cells (1.19 ± 0.04)[52]. The difference is presumably due to the different characteristics of the cells such as type of receptors, number of mitochondria, chromatin structure, all of which affect radiation sensitivity.Mitochondria play a role in regulating the oxidative stress level inside cells.…”
mentioning
confidence: 97%